Quantifying Iconicity’s Contribution during Language Acquisition: Implications for Vocabulary Learning - Massaro, Dominic W.; Perlman, Marcus (Frontiers in Communication, 2017)
Previous research found that iconicity – the motivated correspondence between word form and meaning – contributes to expressive vocabulary acquisition. We present two new experiments with two different databases and with novel analyses to give a detailed quantification of how iconicity contributes to vocabulary acquisition across development, including both receptive understanding and production. The results demonstrate that iconicity is more prevalent early in acquisition and diminishes with increasing age and with increasing vocabulary. In the first experiment, we found that the influence of iconicity on children’s production vocabulary decreased gradually with increasing age. These effects were independent of the observed influence of concreteness, difficulty of articulation, and parental input frequency. Importantly, we substantiated the independence of iconicity, concreteness, and systematicity--a statistical regularity between sounds and meanings. In the second experiment, we found that the average iconicity of both a child's receptive and expressive vocabulary diminished dramatically with increases in vocabulary size. These results indicate that iconic words tend to be learned early in the acquisition of both receptive and expressive vocabulary. We recommend that iconicity be included as one of the many different influences on a child’s early vocabulary acquisition.